Surface Study in a Non-conventional (Electrical Discharge Machining) Process for Grade 6 Titanium Material - Md. Ashikur, Rahman Khan; M. M., Rahman (Penerbit Universiti Teknologi Malaysia, 2014)

(untitled)
Electrical discharge machining (EDM) produces complex shapes and permits high-precision machining of any hard or difficult-to-cut materials. The performance characteristics such as surface roughness and microstructure of the machined face are influenced by numerous parameters. The selection of parameters becomes complicated. Thus, the surface roughness (Ra) and microstructure of the machined surface in EDM on Grade 6 titanium alloy are studied is this study. The experimental work is performed using copper as electrode material. The polarity of the electrode is maintained as negative. The process parameters taken into account in this study are peak current (Ip), pulse-on time (Ton), pulse-off time (Toff), and servo-voltage (Sv). A smooth surface finish is found at low pulse current, small on-time and high off-time. The servo voltage affects the roughness diversely however, a finish surface is found at 80 V Sv. Craters, cracks and globules of debris are appeared in the microstructure of the machined part. The size and degree of craters as well as cracks increase with increasing in energy level. Low discharge energy yields an even surface. This approach helps in selecting proper process parameters resulting in economic EDM machining.